Sectarianism and Difference of Opinion: An Islamic Perspective - Dr. Zaid Malik (MEI, 2023)
The modern world has witnessed its fair share of war and bloodshed due to supremacist ideas and intolerance of diversity, where the greatest of loss is incurred upon the common man. Perhaps, as a lesson learnt from these atrocities, there are numerous multi-national organizations that have come out of their self-created cocoons and have started embracing all of humanity. Sectarianism can arguably be termed one of the greatest issues that the Muslim Ummah is currently facing. When Islam was revealed to our Holy Prophet (SAW) more than 1400 years ago, there was a single way of life that was preached to the new Muslims – and that was the way of the Prophet Muhammad (SAW). This paper will try to differentiate between Sectarianism and difference of opinion, elaborate the stance of Islam on sectarianism and difference of opinion and shed light on the nature, issues and ground realities of sectarianism in Pakistan. The author will also touch on the etiquettes of disagreement in Islam. The paper will investigate an important question: Is it possible for us as Muslims, to stand united despite permissible differences in opinions and respect each other? Are there ways, means or methods that may let us avoid sectarianism or violence while still having our difference of opinions? The research will be based on descriptive and analytical methods.